The impact of orthodontic treatment on the quality of life of patients with malocclusion (Research, Society and Development, 2023)
Introduction: Dental malocclusion is an abnormal alignment of the teeth that impacts the quality of life of patients and treatment aims to reduce these impacts. Objective: to evaluate the implications of orthodontic treatment for the quality of life of patients. Methodology: this is an integrative literature review where searches for scientific evidence were carried out in the databases: Virtual Health Library, Scientific Electronic Library Online and PubMed, using the following descriptors: Malocclusion, Orthodontics and Quality of Life. Results: Initially, 559 articles were found and after applying the exclusion criteria, 7 articles were found that were suitable for the purposes of the study and with a satisfactory degree of scientific evidence. Conclusion: it is concluded that there is a real impact on the quality of life of patients with malocclusion treated orthodontically, both in aesthetic and functional demands.